Methyl jasmonate and salicylic acid synergism enhances phloroglucinol content in shoot cultures of Astragalus fruticosus Forssk - Zayed, Rawia; El-Sayed, Ashraf; Elissawy, Ahmed M.; Ismaeil, Wafaa; El-Shazly, Mohamed; Fayez, Shaimaa (Frontiers in Natural Products, 2025)
IntroductionAstragalus fruticosus Forssk. is a plant species with potential for producing valuable secondary metabolites, such as phloroglucinol, which has pharmaceutical applications. In vitro techniques, including multiple shoot induction and elicitation, offer promising methods to enhance the production of such compounds. This study investigates the use of signal molecules methyl jasmonate (MJ) and salicylic acid (SA) to increase phloroglucinol yield in cultured shoots of A. fruticosus.MethodsStem and leaf explants of A. fruticosus were cultured on Murashige and Skoog (MS) medium supplemented with 1 mg/L 6-benzylaminopurine (BAP) for over 8 weeks to induce multiple shoots. Elicitation was performed by treating the cultured shoots with MJ and SA at concentrations of 50 and 100 μg/mL, individually and in combination (final concentration of 50 μg/mL), over 1–3 weeks. Phloroglucinol content and biomass production were measured to assess the efficacy of the elicitation treatments.ResultsElicitation with MJ at 100 μg/mL resulted in a 5.06-fold increase in phloroglucinol content after 3 weeks compared to the unelicited control. Other treatments with MJ, SA, and their combination also enhanced phloroglucinol production, though to a lesser extent. The highest biomass production was observed under the same conditions that maximized phloroglucinol yield.DiscussionThis study represents the first report of elicitation in A. fruticosus multiple shoot cultures using MJ and SA to enhance phloroglucinol production. The significant increase in phloroglucinol content, particularly with 100 μg/mL MJ, highlights the effectiveness of elicitation as a yield enhancement strategy. These findings suggest potential for optimizing in vitro protocols for large-scale production of phloroglucinol, offering valuable insights for biotechnological applications in pharmaceutical development.